'Saint-Making' in a South Asian Tradition of Islam. (July 2019) - Singh, David Emmanuel
This article relies entirely on the most significant primary sources and uses a phenomenological method of enquiry. It describes the stages that novices journey through in spiritual practice to 'see God' and to engage in what they describe as reports/testimonies and/or revelatory speech. Recognizing the location of the sect within the Mahdist/millenarian movements in Islam, the author points readers in the direction of possible parallels with other charismatic phenomena which could be further explored for intra- and inter-religious dialogue. The author, however, aims to conduct this type of comparative examination in a separate article.